SHOTHAHARA ACTIVITIES OF DASHAMOOLA DRAVYAS AS AN ANTI INFLAMMATORY FORMULATION WITH SPECIAL REFERENCE TO CHARAK- A REVIEW (AYUSHDHARA, 2016)
In Ayurveda texts, Charak Samhita deals with 50 different group of 10 herbs each with specific action and uses. It also deals with different basic formulations like Swarasa (juice), Kalka (paste), Kashaya (decoction) etc. Dashamoola is one of such 50 group of herbs as the name contains root of ten different plants i.e. Bilva, Gambhari, Shyonaka, Patala, Agnimantha, Prishniparni, Salparni, Kantakari, Vrihati & Gokshura. Of these, first five’s are known as Brihad panchamoola and the remaining as Laghoo panchamoola. It is used in the form of Kwath or  Arishta (fermented decoction) or Kashaya according to Ayurveda. This formulation is used primarily for headache, relief of pain and swelling related to arthritis, pyrexia, abdominal distension and costo-chondral pain etc. It is also described as an analgesic used in arthritis and rheumatic conditions by the Ayurvedic practitioners. It is believed that the 10 ingredients of  Dashamoola may be serving different roles like adjuvant, carrier agent and stabilizer etc. evident from several studies. After reviewing the different published literatures studies on experimental models have shown to possess anti-inflammatory and anti-analgesic activities which are enumerated in this paper.